Entrevista a adolescentes con participación de sus padres - Silva Cruz, Julio (2006)
Bases on his experience as a psychotherapist of adolescents, the author proposes the importance of making interviews with parents and adolescents, especially in the process of diagnosis, that was on the side of greater advances in the course of the therapy. The contact modality with parents provide valuable information about the familiar context, the links and the conflicts, important data for a treatment favorable.